A STUDY OF MORAL TEACHING IN THE FUNERAL RITES OF BUDDHISTS IN THA SALA DISTRICT, NAKHON SI THAMMARAT PROVINCE - Chinavaro (Saniya), Phra Chatcharit; Tachathammo (Keawmanee), Phrakru Wijitsathuros; Anuwutthano (Panpradit), Phrakru Kositwattananukul; Chatawunno (Kitikora), Phrakru Wijitsilajarn; Panasree, Sitthichok (Journal of MCU Nakhondhat, 2024)
This research aimed 1) To study the funeral rite in Theravada Buddhist scriptures, 2) To investigate the funeral rite of Buddhists in Tha Sala District, Nakhon Si Thammarat Province, and 3) To explore the moral virtue in the Buddhist funeral ritesTha Sala District, Nakhon Si Thammarat Province. This qualitative research consists of a study of documentary data and in-depth interviews with 20 people. Findings were as follows: 1) Death is a common phenomenon, and its essence can be used to create good things as a reminder not to be careless. It is used to teach the Dharma and put it into practice until one achieves success in life and spiritual attainment. 2) The funeral rites in Tha Sala District community, the tradition of treating corpses and making merit to dedicate to the deceased is the identity of the community. Currently, the tradition of organizing funeral services in the community has changed according to the trend. 3) The moral teaching obtained from the funeral services is mindfulness without carelessness, realizing the truth in the Pancakhandha. Treating corpses explains morality, namely gratitude, respect, and Tilakkhana (Three signs). This ceremony is to dedicate merits and to show kindness to each other. The tradition of ordination in front of cremation indicates moral value about gratitude and it is the way to accumulate the various virtues which are the noble wealth. Funeral rite teaches moral virtue, the truth of life, including impermanence, suffering, non-self, named Three Characteristics Rule. It is carelessness in life, and the tradition of collecting ashes, making merit to dedicate to the deceased teach the moral of gratitude and rebirth. By the power of merit and charity dedicated to the deceased, the deceased will be reborn in a good realm continue investigating.